Russian Federation : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2004)
This report on the Russian Federation's Observance of Standards and Codes reports on the fiscal transparency module. Russia has achieved considerable progress in fiscal transparency and financial management since 1999, although a number of important reforms remain to be undertaken. The legal framework of the budget and tax system as well as for intergovernmental relations has been reformed. Macroeconomic policy forecasts are soundly based and open for scrutiny. Budget preparation has become sophisticated, with considerable transparency in the process and in the availability of information.